2014
DOI: 10.1007/s12032-014-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated antigen genes: a new trend to predict the prognosis of breast cancer patients

Abstract: MAGE-A are normally expressed in testis and placenta. Among MAGEs, the MAGE-A subtype has been the most characterized in cancers. Our study was conducted to assess the expression of (MAGE-A1-MAGE-A6) m-RNA using MMRPs and MAGE-A12 m-RNA in blood for evaluating their clinical implications in breast cancer patients. RT-PCR was carried out to detect the expression of (MAGE-A1-MAGE-A6) m-RNA using MMRPs and MAGE-A12 m-RNA in blood. The study included 100 breast cancer cases aged 41-62 years and 100 controls aged 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Aberrant over-expression of MAGEA12 has been identified in oral squamous cell carcinoma and breast cancer [14,15]. Interestingly, MAGEA12 mRNA can be detected in the blood of 13% breast cancers, and may be used as a biomarker to monitor the progression and therapeutic effectiveness [15]. In this study, we further identified MAGEA12 expression as a novel predictor for the outcome of gastric cancers.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Aberrant over-expression of MAGEA12 has been identified in oral squamous cell carcinoma and breast cancer [14,15]. Interestingly, MAGEA12 mRNA can be detected in the blood of 13% breast cancers, and may be used as a biomarker to monitor the progression and therapeutic effectiveness [15]. In this study, we further identified MAGEA12 expression as a novel predictor for the outcome of gastric cancers.…”
Section: Discussionmentioning
confidence: 62%
“…Yamada et al [13] found that MAGEA12 showed high expression in cancer stem cells, a subgroup with a typical outlier distribution within tumors. Aberrant over-expression of MAGEA12 has been identified in oral squamous cell carcinoma and breast cancer [14,15]. Interestingly, MAGEA12 mRNA can be detected in the blood of 13% breast cancers, and may be used as a biomarker to monitor the progression and therapeutic effectiveness [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observation of ELIspot response to MAGE-A1 in breast cancer is intriguing since there are recently reports of immunogenicity of MAGE-A1 for breast cancer patients [ 57 60 ]. It was previously reported that 27% of breast tumors are positive for at least one of the MAGE transcripts and MAGE expression was more common in ductal breast cancer and Ki-67 high tumors [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next to these mutation-specific neoantigens, other tumor-associated antigens (TAA) are autoantigens which are expressed excessively, differentiation-specific antigens, cancer testis genes (CTA) that display normal expression in immune-privileged organs but aberrant expression in several types of cancer including BC-modified autoantigens, TAA that are highly expressed in tumors such as HER2/neu, and viral-associated antigens. For example, members of the CTA family of melanoma-associated antigens (MAGEs), MAGE-A9 and MAGE-A11, are less expressed in estrogen receptor(ER)-negative and HER2/neu-negative BC [13,14]. In contrast, upregulation of MAGE-A9 in invasive ductal BC is correlated with an unfavorable outcome for patients [15].…”
Section: Breast Cancer and Tumor-associated Antigensmentioning
confidence: 99%